Novel regenerative braking method for transient torsional oscillation suppression of planetary-gear electrical powertrain. (15th January 2022) - Wang, Feng; Ye, Peng; Xu, Xing; Cai, Yingfeng; Ni, Shaoyong; Que, Hongbo
Highlights: Torsional dynamic model of PGEP with angle-varying mesh stiffness and tooth backlash. Transient oscillation analysis during regenerative braking transition process. Optimized torsional vibration-induced regenerative braking method designed and tested. Abstract: Electric regenerative braking systems have drawn much attention in the trends of energy-saving and emission-reduction requirements for electric vehicles. However, the significant differences between regenerative braking transmission chains and the traditional ones have lead to increasing oscillation and noise of electrical powertrain. With the application of planetary-gear transmission chains, adopting an advanced regenerative braking method becomes practical. This paper develops a novel regenerative braking method for transient torsional oscillation suppression of planetary-gear electrical powertrain (PGEP), which uses an angle-varying mesh stiffness-considered transmission model and a genetic algorithm-based method for allocation of electric regenerative braking torque. Simulations are conducted with various angle-varying mesh stiffness and backlash to compare the transient torsional oscillation-suppression performance of PGEP during regenerative braking transition process. For an initial speed of 80 km/h, simulation results show that the proposed torsional oscillation-considered electric regenerative braking torque allocating method performs the best comparing with the traditional methods, which has a 55% reduction in vehicle jerk and 36% improvement in torsional oscillation of PGEP. The AVL experiment results also demonstrated that torsional oscillation-considered regenerative braking method has considerable benefits in both transient torsional oscillation suppression of PGEP as well as enhancement of driving comfort.